Pore-scale investigation of methane hydrate phase transitions and growth rates in synthetic porous media - Lysyy, Maksim (The University of Bergen, 2018)
A growing demand for energy and natural gas in particular, makes methane gas hydrates a potential target to supplement natural gas production from conventional resources. Several pilot projects have proven the feasibility of gas production from hydrates both onshore and offshore, but the proposed models of gas hydrate behavior in sediments lack experimental support. In particular direct pore-scale observations of gas hydrate phase transitions can assist in a better understanding of the fundamentals of gas hydrate phase transitions in sedimentary systems. In this thesis, methane gas hydrate formed from methane gas and distilled water was visually investigated in high-pressure micromodel based on a thin section of Berea sandstone. The main objective of this work was to supplement previous research at the Reservoir Physics groups to determine hydrate formation and dissociation mechanisms on pore scale; and to estimate the hydrate growth rates. Fifteen primary and twenty-two secondary hydrate formation experiments were performed in this work. The first seven primary formations were carried out with initial water saturation ranging from 0.30 to 0.60 and nearly constant pressure (83-84 bar) and temperature (1.2-1.4 °C), with the main intention to study the hydrate formation mechanisms and the effect of initial water saturation and pore sizes on the hydrate growth rates. The remaining experiments were conducted at various pressure-temperature conditions to further investigate formation mechanisms and provide growth rate measurements as function of driving force (degree of subcooling). The hydrate formation was first observed in the continuous water-gas interface, followed by hydrate growth into trapped gas. For both gas configurations, the hydrate growth initiated at the water-gas interface along the pore walls and then progressed towards the pore center. The hydrate growth resulted in two different hydrate configurations: crystalline hydrate with total gas consumption and hydrate films/shell with enclosed gas. Hydrate ...